Konstruksi Pendidikan Islam Moderat Melalui Nalar â€œA Common Wordâ€ Waleed El-Ansary - Muhammad Fahmi; Saefullah Azhari; Syaifuddin; Muhammad Fladimir Herlambang (TADRIS: Jurnal Pendidikan Islam, 2021)
This paper seeks to understand the construction of moderate Islamic education in Waleed El-Ansary's "A Common Word" and its implications for world peace. By library research with content analysis, several idea constructs were proposed. Reason "A Common Word" Waleed El-Ansary is equivalent to "al-Kalimah al-Sawa". This term has the connotative meaning that everything is equal, balanced and equal. The construction of moderate Islamic education can be done through the logic of "A Common Word" as stated by religious leaders, including Waleed El-Ansary. "A Common Word" suggests an intersection or similarity in the teachings of the world's religions, especially Islam and Christianity. When Islam promotes the principle of equality, the teachings developed in Islamic education are Islamic teachings that are moderate, tolerant and full of environmentally friendly nuances. Reason "A Common Word" which contains moderate Islamic teachings (rahmatan li al-aminalamin) can be implemented to achieve world peace. The application of the teaching "A Common Word", has implications for the realization of world peace. Reason "A Common Word", which contains a construction of moderate Islamic education, considers that promoting equality (kalimatun sawa), can be achieved through good relations with others, instilling love, removing hatred, and the like. The construction of moderate Islamic education in reason â€œA Common Wordâ€ has significant implications for world peace. Paper ini berusaha memahami konstruksi pendidikan Islam moderat dalam nalar â€œA Common Wordâ€ Waleed El-Ansary dan implikasinya bagi perdamaian dunia. Melalui kajian kepustakaan dengan analisis isi, dikemukakan beberapa konstruksi ide. Nalar â€œA Common Wordâ€ Waleed El-Ansary semakna dengan â€œal-Kalimah al-Sawaâ€™â€. Term ini memiliki makna konotatif bahwa segala sesuatu bersifat setara, seimbang dan selevel. Konstruksi pendidikan Islam moderat dapat dilakukan melalui nalar â€œA Common Wordâ€ sebagaimana yang dikemukakan oleh para pemuka agama, termasuk Waleed El-Ansary. â€œA Common Wordâ€ meng-ideasikan adanya titik temu atau kesamaan ajaran agama-agama di dunia, terutama Islam dan Kristen. Ketika Islam mengedepankan asas kesamaan, maka ajaran yang dikembangkan dalam pendidikan Islam adalah ajaran Islam yang moderat, toleran dan penuh dengan nuansa ramah lingkungan. Nalar â€œA Common Wordâ€ yang di dalamnya mengandung ajaran Islam moderat (rahmatan li al-â€˜Alamin) dapat diimplementasikan untuk mencapai perdamaian dunia. Penerapan ajaran â€œA Common Wordâ€, berimplikasi pada terwujudnya perdamaian dunia. Nalar â€œA Common Wordâ€, yang di dalamnya mengandung konstruksi pendidikan Islam moderat, memandang bahwa mengedepankan persamaan (kalimatun sawa), dapat dicapai melalui hubungan baik dengan sesama, menanamkan rasa cinta, membuang kebencian, dan sejenisnya. Konstruksi pendidikan Islam moderat dalam nalar â€œA Common Wordâ€ berimplikasi signifikan bagi perdamaian dunia.